Pertumbuhan ekonomi dan ketimpangan di Indonesia periode 2012-2023 - Sari, Pinky Hamdhan; Santoso, Rokhedi Priyo (Jurusan Ilmu Ekonomi, Fakultas Bisnis dan Ekonomika, Universitas Islam Indonesia, 2024)
Purpose – This research has three objectives. First, it analyzes regional economic characteristics regarding economic growth and personal income inequality within a region. Second, it examines the pattern of regional income inequality in Indonesia. Third, it analyzes the correlation trend between regional economic growth and income inequality from 2012 to 2023.Methods – This research uses inequality Klassen Typology, Williamson Index, and Pearson correlation to examine economic growth and income inequality. The secondary data sources are Indonesia's Central Statistics Agency (BPS) for 2012-2023.Findings – Almost half of the provinces in Indonesia are classified as having lower economic growth and lower inequality, called inclusive economies. However, income inequality across provinces has steadily increased recently, especially from 2017 to 2023. The results also show a tendency for a negative correlation between economic growth and income inequality, even though this correlation is not statistically significant. Implication – The Indonesian government should improve the economy's productivity through investment, infrastructure and human capital development while maintaining the redistributive policy and social welfare programmes. Originality – This study comprehensively analyzes recent economic growth in Indonesia in correlation to personal and regional income inequality. AbstrakTujuan – Penelitian ini memiliki tiga tujuan. Pertama, menganalisis karakteristik ekonomi regional terkait pertumbuhan ekonomi dan ketimpangan pendapatan antar individu di suatu wilayah. Kedua, mengkaji pola ketimpangan pendapatan regional di Indonesia. Ketiga, menganalisis tren korelasi antara pertumbuhan ekonomi regional dan ketimpangan pendapatan dari tahun 2012 hingga 2023. Metode – Penelitian ini menggunakan Tipologi Klassen Ketimpangan, Indeks Williamson, dan korelasi Pearson untuk mengkaji pertumbuhan ekonomi dan ketimpangan pendapatan. Sumber data sekunder adalah Badan Pusat Statistik (BPS) Indonesia tahun 2012-2023.Temuan – Hampir setengah dari provinsi di Indonesia tergolong memiliki pertumbuhan ekonomi dan ketimpangan yang lebih rendah, yang disebut ekonomi inklusif. Akan tetapi, ketimpangan pendapatan antar provinsi terus meningkat dalam beberapa tahun terakhir, terutama dari tahun 2017 hingga 2023. Hasil penelitian juga menunjukkan kecenderungan korelasi negatif antara pertumbuhan ekonomi dan ketimpangan pendapatan, meskipun korelasi ini tidak signifikan secara statistik.Implikasi – Pemerintah Indonesia harus meningkatkan produktivitas ekonomi melalui investasi, infrastruktur, dan pengembangan sumber daya manusia dengan tetap mempertahankan kebijakan redistributif dan program kesejahteraan sosial.Orisinalitas – Studi ini menganalisis secara komprehensif pertumbuhan ekonomi terkini di Indonesia dalam kaitannya dengan ketimpangan pendapatan perorangan dan maupun antar provinsi